2005
DOI: 10.1002/adsc.200505190
|View full text |Cite
|
Sign up to set email alerts
|

The Direct, Enantioselective, One‐Pot, Three‐Component, Cross‐Mannich Reaction of Aldehydes: The Reason for the Higher Reactivity of Aldimine versus Aldehyde in Proline‐Mediated Mannich and Aldol Reactions

Abstract: In the proline-mediated Mannich and aldol reactions of propanal as a nucleophile, the aldimine prepared from benzaldehyde and p-anisidine is about 7 times more reactive than the corresponding aldehyde, benzaldehyde, as an electrophile. This higher reactivity of aldimine over aldehyde is attributed to the carboxylic acid of proline protonating the basic nitrogen atom of the aldimine more effectively than the oxygen atom of the aldehyde, an explanation which has been both experimentally and theoretically verifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 97 publications
1
10
0
Order By: Relevance
“…Hayashi and co-workers have suggested that the more basic imines are more readily activated by the carboxylic acid of proline. 47 …”
Section: Enamine/iminium Catalysismentioning
confidence: 99%
“…Hayashi and co-workers have suggested that the more basic imines are more readily activated by the carboxylic acid of proline. 47 …”
Section: Enamine/iminium Catalysismentioning
confidence: 99%
“…In general, it is quite difficult to control the high reactivity of acetaldehyde. An acid activates the imine selectively rather than the aldehyde8c and promotes the Mannich reaction efficiently, whereas the reactivity of the enamine is reduced with suppression of the generation of an enamine from the product, which reduces the overall reactions, because of the bulkiness of catalyst 1 . The Mannich reaction catalyzed by bulky organocatalyst 1 , combined with acid additives, distinguishes it from the proline‐mediated reaction 7a…”
Section: Methodsmentioning
confidence: 99%
“…In our work [27][28][29][30][31][32][33], reactions were conducted using acetaldehyde and N-benzoyl-Nbenzylidene amine (29) as model substrates, and a diarylprolinol silyl ether as the key catalyst; the resulting b-amino aldehyde product 30 was isolated by its conversion into the corresponding alcohol by reduction with LiAlH 4 . When proline 16 was employed as the catalyst, excellent enantioselectivity was obtained in CH 3 CN with moderate yield, due to competitive hydrolysis of the imine under the acidic conditions.…”
Section: Acetaldehyde As Nucleophilementioning
confidence: 99%